Pemanfaatan Ampas Tahu Sebagai Pakan Ikan Lele (Clariasbatrachus) Organik - Dewi Nur Anggraeni; Rahmiati Rahmiati (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2016)
This research was aimed to use tofu as organic feed for catfish and thus to create a product of organic fish feed made of tofu. Research was done in four steps, (I) Preparation of materials andequipment, (II) Production of organic fish feed, (III) Analysis of carbohydrate, protein, and lipidcontent in organic fish feed, (IV) Measurement of catfish weight. The parameters observed in thisstudy are carbohydrate, protein, and lipid content of organic catfish feed, and the weight of organiccatfish. Organic fish feed made from 100% tofu dreg was used as control (AT0). Feed used fortreatment were made of tofu dreg-fish head (AT1), tofu dreg shrimp head (AT2), and tofu dreg-bran(AT3). The result showed that the best treatment to produce organic fish feed were AT1 (42.01%)and AT2 (43.05%) which showed high content of carbohydrate, protein, and lipid. Based ongrowth, AT1 and AT2 also showed the best percentage rate of growth and survival. AT2 treatmentshowed greater weight than AT1 but not significantly different.